Outbreak of West Nile Virus disease in Israel (2015): A retrospective analysis of notified cases. Issue 28 (March 2019) - Salama, Matanelle; Amitai, Ziva; Lustig, Yaniv; Mor, Zohar; Weiberger, Miriam; Chowers, Michal; Maayan, Shlomo; Zimhony, Oren; Ben-Ami, Ronen; Chazan, Bibiana; Zaltzman-Bershadsky, Nelly; Cohen, Regev; et al.
Abstract: Background: West Nile Virus (WNV) is mosquito-borne virus that is endemic in Israel. In 2015, national disease surveillance demonstrated a sharp increase in disease cases, with 149 cases diagnosed. Methods: Clinical data was extracted from the patients' medical files and laboratory analysis on blood, cerebrospinal fluid or urine was carried out. Data on climate was extracted from the Israel Meteorological Service. Results: Neuroinvasive disease was reported in 70% of cases and case-fatality rate was 16%. Simultaneously with the outbreak, an intense heat wave and an upsurge in summer temperatures occurred. Conclusions: Clinical data shows substantial morbidity and mortality of WNV disease in Israel. Climatic measures are consistent with previous reports and point to the importance of temperature monitoring and rapid implementation of preventive environmental measures during the summer to reduce potential mosquito breeding sites. WNV disease should be suspected as a cause of fever or neurologic disease in travelers returning from endemic countries.